Makam Seniman: Perkembangan Identitas Pemakaman di Era Modern - Benny Afwadzi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
The paper examines the development of grave identity in the modern era, which focuses on Taman Makam Seniman dan Budayawan Giri Sapto, which is located on Gajah hill, Giri Rejo village, Imogiri sub-district, Bantul district, Daerah Istimewa Yogyakarta. The grave that full of art elements is very interesting because it is devoted to artists and cultural observers and also does not recognize the exclusivity of certain religions, becomes a tourist destination in Yogyakarta, and is mentioned as the only one in the world. This study used field research, with qualitative-descriptive methods and data collecting techniques in the form of observation, interviews, and documentation. The author finds that the artists’ grave (Makam Seniman) are grave with a characteristic exclusivity of certain professions (artists) and also store interesting artistic elements, namely the existence of several gravestones with unique shapes which symbolizes the art field of the deceased when it was still alive, the artwork displayed on the grave, and the funeral ceremony combined with art. Seeing the phenomena that created from this grave, it can be said that there has been a form of grave identity development in modern times due to the development of human culture, which in the context of the artists’ grave is realized by art. Artists’ grave essentially contains the development of identity as a grave place, which previously had appeared a grave with a model of religious identity, Pancasila (multi religions), heroes, kingdoms, and even pesantren. This type of grave identity with the model that is following a profession or a field that occupied by someone can be said to become a characteristic of the modern grave culture.